Multidetector Tomography in Cases with Major Chest Trauma - Atanas Hilendarov; Gergiev Alexander; Cherenkov Lyubomir; M. U. Plovdiv (Current Practice in Medical Science Vol. 7, 2022)
This article summarizes the place of Multidetector computed tomography (MDCT) in the diagnosis, examination technique and findings in injuries of the major chest trauma patients. The most efficient imaging technique in this area is MDCT. Its advantages include especially high speed and high geometric resolution at any plane. With the use of this technique, we may accurately produce multiplanar and three-dimensional (3D) reformations while viewing sizable portions of the body with the fewest motion artefacts possible. MDCT allows us to view diagnosis significantly more accurate. A total of 112 individuals are examined in the emergency department. The intrathoracic organs are injured, as well as the chest. Rib fractures are the most frequent traumas in 56 (or 50%) of the 112 individuals in our study. Injuries to blood vessels as well as fractures of the scapula, sternum, extra pleural hematomas, pneumothorax, hemothorax, pulmonary contusions, laceration of the trachea and bronchi, rupture of the oesophagus, and hemothorax are also documented. Due to its benefits, MDCT has risen to the top of the list for treating acute chest trauma patients.